The Implementation of the Family Hope Program (PKH) During the Pandemic in Batu City - Muhammad Zaini; Asep Nurjaman (Universitas Medan Area, 2022)
The purpose of the study was to find out that the Family Hope Program was carried out according to its purpose, namely eradicating poverty during a pandemic. The problem is focused on the implementation of the Family Hope Program (PKH) during the pandemic which has an impact on increasing poverty rates. To approach the problem. The research uses the theory of Merilee S. Grindle to build a network that allows public policy goals to be realized as a result of government activities. The research was carried out qualitatively with a descriptive approach to solving problems. The results showed that the Family Hope Program during the pandemic increased, but did not reach all affected families due to data synchronization problems. This finding indicates that the implementation of the Family Hope Program run by the Batu City Social Service is not going well.